2022
DOI: 10.1590/1516-4446-2020-1709
|View full text |Cite
|
Sign up to set email alerts
|

Neurocircuit models of obsessive-compulsive disorder: limitations and future directions for research

Abstract: Obsessive-compulsive disorder (OCD) is a common psychiatric condition classically characterized by obsessions (recurrent, intrusive and unwanted thoughts) and compulsions (excessive, repetitive and ritualistic behaviors or mental acts). OCD is heterogeneous in its clinical presentation and not all patients respond to first-line treatments. Several neurocircuit models of OCD have been proposed with the aim of providing a better understanding of the neural and cognitive mechanisms involved in the disorder. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 135 publications
(177 reference statements)
0
16
0
Order By: Relevance
“…A recently published review highlights the importance of the PFC in the etiology of OCD symptoms. 42 One theory is that deficits in a PFC cognitive control network (such as the dorsal cognitive CSTC circuit described in previous neurocircuitbased models of OCD 4,5,43 ) could lead directly to compulsions, because hypoactivity could cause impairments in inhibitory control and automatic engagement in compulsive behaviours, particularly in stressful circumstances. Hyperactivity in PFC regions at baseline and during symptom provocation is thought to reflect compensatory responses that boost performance of critical PFC executive control functions, including decision-making and goal-directed planning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published review highlights the importance of the PFC in the etiology of OCD symptoms. 42 One theory is that deficits in a PFC cognitive control network (such as the dorsal cognitive CSTC circuit described in previous neurocircuitbased models of OCD 4,5,43 ) could lead directly to compulsions, because hypoactivity could cause impairments in inhibitory control and automatic engagement in compulsive behaviours, particularly in stressful circumstances. Hyperactivity in PFC regions at baseline and during symptom provocation is thought to reflect compensatory responses that boost performance of critical PFC executive control functions, including decision-making and goal-directed planning.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should include ROIs related to the dorsal cognitive CSTC circuit (including the dorsal aspects of the PFC), given the current neurocircuit-based models of OCD 4,5,43 and this circuit's implication in executive function, such as working memory and planning, as well as emotion regulation. 4…”
Section: E417mentioning
confidence: 99%
“…In turn, these signals of abnormal network activity normalize with usual treatment and/or predict disease progression or recovery. 17,[19][20][21][22][23] In a recent systematic review of the neural correlates of well-being, 11 studies used qEEG (measuring the EEG power) to link well-being to regional brain activation, suggesting that a larger α asymmetry (more activation on the brain's left side than on the right) is related to greater well-being, according to the neuropsychological theory of lateralized affective function. 24 With the aim of using EEG profiles as a biomarker of wellbeing, Chilver et al 25 examined the association between mental well-being and EEG power (delta, theta, α and β) in 422 healthy adults using linear mixed models.…”
Section: Measuring Subjective Well-being: Positive Emotions and Brain...mentioning
confidence: 99%
“…In turn, these signals of abnormal network activity normalize with usual treatment and/or predict disease progression or recovery. 17 19 20 21 22 23…”
Section: Measuring Subjective Well-being: Brain Oscillationsmentioning
confidence: 99%
“…Recent neuroimaging studies have shown that the standard cortico-striato-thalamo-cortical (CSTC) model alone may be inadequate to explain this heterogeneity (Milad and Rauch 2012) and indicated evidence for the involvement of wider cortical and subcortical structures beyond the CSTC circuit (Menzies et al 2008; van den Heuvel et al 2016). It has been postulated that the diverse clinical presentations and the associated neurocognitive deficits may be explained by the varied involvement of the dorsal cognitive, ventral cognitive, fronto-limbic, sensorimotor, and frontoparietal networks (Shephard et al 2021; 2022).…”
Section: Introductionmentioning
confidence: 99%